Maxillary protraction effectiveness in adolescents with cleft palate: A systematic review and network meta-analysis - Madawana, Ashwini M.; Ruslan, Ahmad Hashridz; Nawi, Mohamad Arif Awang (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Adolescent patients with maxillary hypoplasia due to cleft may benefit from maxillary protraction therapy. Purpose: This review aimed to evaluate and compare the clinical outcomes of different maxillary protraction methods in adolescents with cleft palate through a systematic review and network meta-analysis. Methods: Relevant studies were identified through electronic searches of the PubMed, Scopus, and Web of Science databases up to 2024. Randomized and controlled clinical trials assessing maxillary protraction outcomes in this population were included. Risk of bias was evaluated, and pooled data were analyzed using a random-effects model and network meta-analytic techniques. Results: The post-treatment results of A-VRP, ANB, A-N perp, Wits, overjet, and SNA landmark mean differences indicate successful correction of class III malocclusion and protrusion of the maxilla. Based on a subgroup study of the face mask with mini-plate (FM-MP) and class III intermaxillary elastic (C3-IE) subgroups, the FM-MP subgroup exhibited more pronounced alterations in SNA, ANB, and overjet features than the C3-IE subgroup. When the outcomes of these two treatment methods were examined, no statistically significant differences were discovered—except for the overjet subgroup. Utilizing class III elastics with bone anchors was less successful in boosting overjet than using FM-MPs. Conclusion: Maxillary protraction therapy is a good substitute for teenagers with cleft lip and palate deformities.